Current advances on the phytochemical composition, pharmacologic effects, toxicology, and product development of Phyllanthi Fructus - Yan, Xiaoyu; Li, Qiuju; Jing, Lin; Wu, Shuangyue; Duan, Wei; Chen, Yan; Chen, Dayi; Pan, Xiaoqi (Frontiers in Pharmacology, 2022)
Phyllanthi Fructus (PF), the edible fruits of Phyllanthus emblica L., serves as an important resource for some health products, foods and drugs due to its high safety and sufficient nutritional value. In recent years, in vivo and in vitro experiments have been conducted to reveal the active components of PF. More than 180 compounds have been isolated and identified from the PF so far, primarily including tannins, phenolic acids, flavonoids, terpenoids, polysaccharides, fatty acids and amino acids. In traditional Chinese medicine (TCM), PF is used to cure several diseases such as bronchitis, asthma, diabetes, peptic ulcer, hepatopathy, leprosy, and jaundice. Consistent with ethnopharmacology, numerous modern studies have demonstrated that the extracts or monomeric compounds derived from PF exhibit various pharmacological effects including anti-oxidation, anti-bacteria, anti-inflammation, anti-tumour, anti-virus, immunity improvement, hypoglycemic and hypolipidemic effects, and multiple organ protective protection. Toxicological studies on PF indicated the absence of any adverse effects even at a high dose after oral administration. Due to strict quality control, these pharmacological activities and the safety of PF greatly improve the development and utilization of products. Our comprehensive review aims to summarize the phytochemistry, pharmacological effects, toxicology, and product development of PF to provide theoretical guidance and new insights for further research on PF in the future.